EKSISTENSI KURIKULUM PESANTREN MU’ADALAH DI ERA GLOBAL - Wawan Setyawan (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2015)
how the curriculum implementation challenges and opportunities after published government regulations about education schools and diniyah through PMA numbers 13 and 18 in 2014th. Curriculum of Boarding school Salaf obtained Mu’adalah or equalization which is using yellow book and the general education curriculum while the curriculum in a modern boarding school known as the Islamic Dirosah Mualimin pattern. It means learning curriculum that applies classical books with the strengthening of the Arabic language in which the learners (students) can independently examine any kind of book in the future. Challenge of Mu’adalah does not require students following national exams.